1977
DOI: 10.1128/aem.34.6.849-853.1977
|View full text |Cite
|
Sign up to set email alerts
|

Development of Poliovirus Having Increased Resistance to Chlorine Inactivation

Abstract: A laboratory strain of poliovirus (LSc) became progressively more resistant to chlorine inactivation during a series of repeated sublethal exposures to the halogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Finally, there remains the possibility of viral adaptation to new environmental conditions. In this context, Bates et al (28) described the development of poliovirus having increased resistance to chlorine inactivation. Clearly, much remains to be learned about the mechanism of viral inactivation by and viral resistance to disinfectants.…”
Section: Mechanisms Of Viral Resistance To Antiseptics and Disinfectantsmentioning
confidence: 99%
“…Finally, there remains the possibility of viral adaptation to new environmental conditions. In this context, Bates et al (28) described the development of poliovirus having increased resistance to chlorine inactivation. Clearly, much remains to be learned about the mechanism of viral inactivation by and viral resistance to disinfectants.…”
Section: Mechanisms Of Viral Resistance To Antiseptics and Disinfectantsmentioning
confidence: 99%
“…Shaffer et al (31) recently demonstrated that poliovirus isolates obtained from fully treated, chlorinated drinking water were several orders of magnitude more resistant to free chlorine than two stock laboratory strains which were used for comparison. Furthermore, evidence has been reported which suggests that repeated exposure of poliovirus 1, strain LSc, to sublethal concentrations of chlorine may lead to physiological or genetic selection for increased resistance to this halogen (3). Some proposed mechanisms by which bacteria and viruses may develop resistance to chlorine include: (i) modification of cell surface structures which may lead to increased aggregation or clumping of cells in situ (11), (ii) microbial adhesion to pipe surfaces or to suspended particulate matter such as detritus or clay particles (34), (iii) extrusion of protective extracellular capsular or slime layers (30), and (iv) formation of resistant spores (14,16,17).…”
mentioning
confidence: 99%
“…Recent laboratory studies have shown that poliovirus 1, strain LSc, will exhibit progressively greater resistance to inactivation by chlorine after repeatedly exposing the virus to sublethal doses of chlorine followed by growth of the survivors in cell cultures (2,3).…”
mentioning
confidence: 99%